Preaching Model for Prospective Hajj Pilgrims at the Ministry of Religious Affairs of Jeneponto Regency - Rika Yuliana; Muliaty Amin; Asiqah Usman (Jurnal Mercusuar, 2022)
This study discusses the Dawah Model for Prospective Hajj Pilgrims at the Ministry of Religious Affairs in Jeneponto District. The main issues and objectives of this research are to identify the Dawah Model applied in that location as well as the effectiveness, efficiency, and challenges faced in the Hajj preparation activities in Jeneponto District. This research employs a combination of descriptive qualitative and case study approaches. The study utilizes both the Dawah and value approaches. Data collection methods involve observation, interviews, and documentation. The collected data is then subjected to reduction, display, and conclusion drawing. Data validity is tested through triangulation. The results of this research are as follows: 1) Effectiveness and Efficiency of Hajj Preparation for Prospective Hajj Pilgrims at the Ministry of Religious Affairs in Jeneponto District encompass: a) Enhancement of Speaker Capacity, b) Material Structuring, c) Polarization and Categorization of Prospective Hajj Pilgrims, d) Classification of Hajj Preparation. 2) The Dawah Model for Prospective Hajj Pilgrims at the Ministry of Religious Affairs in Jeneponto District includes: a) Lectures, b) Practices, and c) Book and E-book Media. The challenges faced in the Dawah Model for Hajj preparation at the Ministry of Religious Affairs in Jeneponto District are primarily related to the diverse capacities of the Hajj pilgrims. The implications of the study are: 1) It is recommended that the guides, in this case, the Jeneponto Ministry of Religious Affairs, maintain their performance in providing appropriate guidance to prospective Hajj pilgrims. 2) Prospective Hajj pilgrims should follow systematic Hajj preparation procedures from the initial guidance until departure, in order to achieve a high-quality worship experience. 3) The government should consider extending the previously established Hajj preparation guidance period to ensure the optimal readiness of the Hajj pilgrims.